1978
DOI: 10.1038/bjc.1978.281
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prostaglandins and hormones on cyclic AMP formation in rat hepatomas and liver tissue

Abstract: Summary.-The formation of cyclic AMP was studied in normal liver, subcutaneous hepatomas derived from MH1C1 cells, and premalignant liver and primary hepatomas induced by the carcinogens 2-acetylaminofluorene (AAF) and 4-dimethylamino-azobenzene (DAB). While only very slight effects of prostaglandins (PG) were seen in slices of normal liver, all the hepatomas responded strongly to PGE1 and PGE2. The hepatomas also had increased PGE,-sensitive adenylate-cyclase activity. PGFia and PGF2as did not increase the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Surprisingly we found an interspecies difference concerning the number of binding sites between rat and human liver. Since rat hepatomas have an increased PGE1-sensitive adenylate cyclase activity and produce increased amounts of cAMP (Allen et al, 1971;Bronstad et al, 1978, Bronstad & Christofferson, 1981, Chayoth et al, 1973 we addressed the question of whether the binding capacity for PGE1 would be affected in human hepatocellular cancers.…”
mentioning
confidence: 99%
“…Surprisingly we found an interspecies difference concerning the number of binding sites between rat and human liver. Since rat hepatomas have an increased PGE1-sensitive adenylate cyclase activity and produce increased amounts of cAMP (Allen et al, 1971;Bronstad et al, 1978, Bronstad & Christofferson, 1981, Chayoth et al, 1973 we addressed the question of whether the binding capacity for PGE1 would be affected in human hepatocellular cancers.…”
mentioning
confidence: 99%
“…It has long been suspected that PGs and cAMP are involved in cell growth and cancer development [99] but this seems to be dependent on which specific PG is involved. PGF1alpha (PGF1a) and PGF2alpha (PGF2a) do not increase cAMP but 2-acetylaminofluorene (AAF)-induced cancer is associated with increased prostaglandin E1 (PGE1) [100].…”
Section: Eicosanoidsmentioning
confidence: 99%
“…Prostaglandins are associated with the activation of the adenylate cyclase-cAMP-system through specifically membrane bound receptors that have been demonstrated in several tissue fractions or at cell surface membranes (e.g., Hall & Strange, 1984, Riicker & Schr6r, 1983Virgolini, 1987). Increased response to prostaglandins by measuring the cAMP content in neoplastic tissue has been observed in various studies (e.g., Bronsted et al, 1978;Chayoth et al, 1973), thus prostaglandins are proposed to take part in cellular growth (Feher & Gridali, 1974;Hial et al, 1976). For thyroid cancer the effects of prostaglandins and of their synthesis inhibitors aspirin or indomethacine have been rarely reported in the literature (Sand et al, 1976), although an alteration in adenylate cyclase activity has been indicated in thyroid cancers (De Rubertis et al, 1972;Orgiazzi et al, 1977).…”
mentioning
confidence: 92%